Plain Language and the Alert on Misuses of Speech in Legal Practice (Milan Law Review, 2024)
This paper argues that there is a problem with the concept of plain language since it is not really language and there is only a pretension of at clarity. It is explained that, although the movement puts the receiver at the centre of the scene, this does not usually materialize in practice. Finally, it is pointed out why these drafting keys apply to both technical and natural language and it is argued that errors of communication should not be legitimized by claiming that they are specific to the legal field and that they can be translated more clearly to another new text. Thus, plain language should be reserved specifically for adapting a message to a particular audience, not for accepting misuse of language under the pretext that it is a professional form of drafting.
Keywords: Legal language; Plain Language; Speech acts